Hubungan Perawat dan Pasien: Implementasi Standar Keselamatan Pasien - Rospita Siregar (to-ra, 2016)
The positive impact by implementing a culture of safety within hospital services will increase patient safety, supported by good communication with patients. unexpected events that arise due to the negligence of nurses could cause injury to the patient, such as Near Miss or Adverse Event (Genesis Unexpected). Thus the complaints and litigation is reduced, service quality increases, the image of hospitals and public confidence increased, advised the hospital to have an attitude to support the implementation of the program of patient safety, through training, it is expected to be effected in increasing motivation and work attitudes of nurses in hospitals Keywords: hubungan perawat dan keselamatan pasien